Concise Review: The Yin and Yang of Intestinal (Cancer) Stem Cells and Their Progenitors. (November 2013) - Stange, Daniel E.; Clevers, Hans
Abstract The intestine has developed over the last few years into a prime model system for adult stem cell research. Intestinal cells have an average lifetime of 5 days, moving within this time from the bottom of intestinal crypts to the top of villi. This rapid self‐renewal capacity combined with an easy to follow (mostly) unidirectional movement of cells offers an ideal site to conduct adult stem cell research. The delineation of the active pathways in the intestinal epithelium together with the development of molecular techniques to prove stemness laid the grounds for the identification of the intestinal stem cell. In vitro systems and transgenic mouse models broaden our knowledge on the role of the stem cell niche and those cells that reestablish homeostasis after perturbation of the system. These insights expedited also research on the role of normal adult stem cells in cancer initiation and the factors influencing the maintenance of cancer stem cells. Stem Cells2013;31:2287–2295